Comunicación y sentido desde una punto de vista cibernético (2010)
ABSTRACT: This article tries to briefly explore the relationship between sense and communication from the standpoint of classic first-order cybernetics. The departing point is the assertion that studies in classic cybernetics create a paradox by mixing up communication and interaction: sense as a subjective process that is made objective, but that can only be understood from the interaction between a sender and a receiver in a concrete situation. Second order cybernetics allows solving this paradox by integrating some cognitive concepts and displacing the observer concept from the sender or the receiver to the processing of information as an operation itself.